Ecological interrelations of mass ground beetles with carabophile mite Anystipalpus livshitsi (Eidelberg, 1989) and Caraboacarus stammeri (Krezal, 1959) in the central part of the steppe zone of Ukraine - Кобеза, П. А.; Пахомов, О. Є. (Problems of Environmental Biotechnology, 2018)
The analysis of seasonal dynamics of mass ground beetles for the central part of the steppe zone of Ukraine within four typical ecosystems is carried out. The species composition of carabidophilic acarose for ground beetles was established: Calathus ambiguus (Paykull, 1790), Calathus fuscipes (Goeze, 1777), Calathus melanocephalus (Linnaeus, 1758), Pterostichus melanarius (Illiger, 1798), Pterostichus melas (Creutzer, 1799), Pterostichus niger (Schaller, 1783). The main invasive species of the carabophile mite are: Anystipalpus livshitsi (Eidelberg, 1989) and Caraboacarus stammeri (Krezal, 1959). The seasonal dynamics of the indices of beetle populations is presented, the analysis of the sexual structure of the population of mass species of carabidofauna is carried out. The results of the analysis of epizootics for males and females of six species of ground beetles within the limits of 4 types of biogeocenosis for seven months of the study are presented. 49 literary sources were processed. In this paper, 8 photographs of the cobbophilic ticks and 12 diagrams are presented.